Psycho-pedagogical approaches to the socialization process of the gifted students in high school - Furdui, S. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2014)
Socialization of gifted students defined as the process by which individuals absorbed the social experience of its social environments o that through the formation of his own "I" shows the uniqueness of the individual as an individual. The leading feature of the socialization of students allocated to the concept of "socialization of gifted students" – a description of the integration of the young person, which includes a set of acquired knowledge, skills, attitudes, and professional and personal qualities sufficient to fully carryout major social roles, the subsequent development of abilities and talents of personality, its successful creative fulfilment.
Keywords: talent; socialization; socialization of a gifted student; social maturity of the student